On Local-Strong Rainbow Connection Numbers On Generalized Prism Graphs And Generalized Antiprism Graphs - Nugroho, Eri; Sugeng, Kiki Ariyanti (Pattimura University, 2022)
Rainbow geodesic is the shortest path that connects two different vertices in graph such that every edge of the path has different colors. The strong rainbow connection number of a graph G, denoted by src(G), is the smallest number of colors required to color the edges of G such that there is a rainbow geodesic for each pair of vertices. The d-local strong rainbow connection number, denoted by lrscd, is the smallest number of colors required to color the edges of G such that any pair of vertices with a maximum distance d is connected by a rainbow geodesic. This paper contains some results of lrscd of generalized prism graphs (PmxCn) and generalized antiprism graphs for values of d=2, d=3, and d=4.